The price you pay [large type] - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel., 2024)
"Lewis has helped Peter Ash out of more trouble than Peter cares to remember. So he doesn't hesitate when Lewis asks a favor in return. Lewis has left his criminal past behind, but they learn that someone has stolen notebooks full of incriminating secrets about his crimes and realize the situation is much worse than they'd thought. To save Lewis' wife, Dinah, and her two boys, Lewis and Peter must find the notebooks. They begin the search - facing ruthless and violent foes at each turn. Will Peter and Lewis be able to keep that dark past buried? Or will they need to step into the darkness to save the people they love most?" --